Peanut Processing Characteristics and Quality Evaluation - Wang, Qiang (Springer Singapore, 2018)
This book systematically covers the sensory, physical, chemical nutrition, and processing characteristics of different peanut varieties, while also providing an in-depth review of research advances in peanut processing quality. The book goes on to examine the relationship between raw materials and the qualities of peanut protein, peanut oil and other main peanut processing products. As such, it provides a valuable reference guide for research into the raw materials, change mechanisms and control technologies used in peanut processing, laying the groundwork for the development of new disciplines in "grain and oil processing quality". It will be useful for graduate students, researchers, and management groups from multidisciplinary audiences, covering both food science & technology and public health.